A PROBIOTIC APPLICATION OF Lactobacillus acidophilus HT1 FOR THE TREATMENT OF SOME SKIN PATHOGENS - & et al., Rasheed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The present study was designed to investigate the possibility of using Lactobacillus as a skin probiotic. For this purpose, 63 isolates of Lactobacillus sp. were collected from dairy products and human mouth samples. The isolates were screened for bacteriocin production by primary and secondary screening against three common skin pathogens. The results showed that the isolate Lactobacillus HT1give the highest productivity of bacteriocin (320AU/ml), the efficient isolate was identified through molecular detection using 16S ribosomal RNA gene. In addition, result showed that L. acidophilus HT1 was un encapsulated; has no capability to produce biofilm and was susceptible to amoxicillin–clavulanic acid, vancomycin and chloramphenicol. Moreover, the infectious dose of L. acidophilus HT1 was studied and results revealed that mice were remained in a healthy condition including all vital processes such as breathing, consuming food and water as well as external and anatomical appearance. Next, an emul gel formula contained L. acidophilus HT1 biomass was prepared which already examined in vitro and in vivo. Our results confirmed the efficacy of the formula via inhibiting the growth of pathogenic isolates and through several points included: viability of L. acidophilus HT1 cells, its ability to produce bacteriocin, and its releasing from the formula to the external environment without trapping or interaction among bacteriocin and any component of formula. In vivo results approved the affectivity of L. acidophilus HT1 biomass to treat the wounds infected with different bacterial pathogens during seven days after the onset of treatment compared with the control groups.